Congenital smooth muscle hamartoma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2014)
Case report. A 1-month-old little girl was first observed due to a dark spot on the right leg present from birth, that had not changed over time. The dermatological examination revealed (Fig. 1) a 3.5 x 2.5 cm patch, regularly oval with larger transverse axis, peripheral erythematous ring and leaden color in the center; on the patch there were longer and darker hairs. The palpation showed no obvious infiltration. Dermoscopy (Fig. 2) showed no melanocytic pattern. We refrained from making a diagnosis and we reviewed the child after 3 weeks: the only differences (Fig. 3) was a less visible hair component and moderate infiltration of the lesion at palpation that allowed us to perceive a thrill reminiscent of smooth muscle hamartoma. At the 3rd visit when the little girl was aged 4 months (Fig. 4) the infiltration increased with the formation of a central fold and at palpation a more marked feeling of contractility.